2000
DOI: 10.1161/01.str.31.8.1929
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Integrated (Managed) Care Pathway for Stroke Rehabilitation

Abstract: Background and Purpose-Integrated Care Pathway (ICP) is an organized, goal-defined, and time-managed plan that has the potential of facilitating timely interdisciplinary coordination, improving discharge planning, and reducing length of hospital stay. Methods-An ICP for stroke rehabilitation based on evidence of best practice, professional standards, and existing infrastructure was developed. Its effectiveness was tested in 152 stroke patients undergoing rehabilitation who were randomized to receive ICP care c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
150
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 27 publications
0
150
1
Order By: Relevance
“…Likewise, S 2 (8) and S 9 (15) presented similar results in this sense; quality of life did not improve with the application of an intervention when comparing two health care models; and a well-structured and monitored program did not show any advantage over a conventional multidisciplinary approach in terms of improved indicators of QoL.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Likewise, S 2 (8) and S 9 (15) presented similar results in this sense; quality of life did not improve with the application of an intervention when comparing two health care models; and a well-structured and monitored program did not show any advantage over a conventional multidisciplinary approach in terms of improved indicators of QoL.…”
Section: Discussionmentioning
confidence: 70%
“…When associating functionality with the perception of HRQoL, S 3 (9) confirms functional, personal/motor and social preservation (among other variables) is related to a better perception of HRQoL, being a significant predictor (S 8 (14) ) for lower hospitalization and mortality rates, also in the long term; on the other hand, it seems insensitive to the approaches experimentally used in one study (S 9 (15) ), whose objective was to evaluate the effectiveness of a structured program (ICP) in the reduction of length of stay, without affecting such functionality. Other studies/comments agree in these different realities; in S 11 (17) , the provision of training to caregivers of patients with stroke improves important aspects of their own lives but has no impact on the functionality of patients (when compared to usual procedures of caregivers without specific training).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Importance of early rehabilitation in patients after stroke is apparent as it increases the possibility of recovery or compensation of dysfunctions (14). Occupational therapy is applied in rehabilitation of patients after stroke (15).…”
Section: Introductionmentioning
confidence: 99%
“…The point in a patient's hospital admission when discharge planning is implemented also varied across studies. 3,4 Two trials reported discharge planning commencing from the time that a patient was admitted to hospital 69,70 and another study reported that discharge planning was implemented 3 days prior to discharge. 71 The timing of delivery of an intervention such as discharge planning, which depends on organising other services, will have some bearing on how quickly these services can begin providing care.…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%